Two new species of the millipede genus Glyphiulus Gervais, 1847 from Southwest China (Diplopoda: Spirostreptida: Cambalopsidae) - Jiang, Xuan-Kong; Lv, Jing-Cai; Guo, Xuan; Yu, Zhi-Gang; Chen, Hui-Ming (Zootaxa, 2017)
Two new Chinese species of the millipede genus Glyphiulus Gervais, 1847, Glyphiulus latus sp. nov. and Glyphiulus liangshanensis sp. nov., from three caves in Sichuan Province are described. According to the structure of the first male leg pair, the new species belong to the javanicus-group.